2022
DOI: 10.1111/jcap.12370
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review into the impact of COVID‐19 pandemic on senior high school adolescent mental health

Abstract: Problem High school teenagers are facing significant challenges during the COVID‐19 pandemic. Teenagers are at risk of experiencing physical, mental, and social health problems due to the COVID‐19 pandemic. This narrative review aims to explore the impact of COVID‐19 on the emergence of mental health problems in high school adolescents. Methods This study employed a narrative review method. We conducted a systematic search using PRISMA on three databases: Medline, PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…However, the transition to online learning might have been challenging for some students for varying reasons (Kadse et al, 2022). Students go through a transitional phase as they have to the different pressures of distance learning, followed by traditional or face-to-face learning once they are back in school (Neal, 2020 as cited in Windarwati et al, 2022).…”
Section: Contained Personal Problemsmentioning
confidence: 99%
“…However, the transition to online learning might have been challenging for some students for varying reasons (Kadse et al, 2022). Students go through a transitional phase as they have to the different pressures of distance learning, followed by traditional or face-to-face learning once they are back in school (Neal, 2020 as cited in Windarwati et al, 2022).…”
Section: Contained Personal Problemsmentioning
confidence: 99%
“…Social connectedness and school disruptions are significantly associated with depressive symptoms ( 8 ). However, adolescents' daily stress events decreased more during the pandemic ( 5 , 7 , 9 , 10 ). A previous study reported that the COVID-19 pandemic increased home- and health-related stress but showed a trend toward lower school-related stress ( 11 ).…”
Section: Introductionmentioning
confidence: 97%
“…The effects of the COVID-19 pandemic on adolescents varied, with some reporting a deterioration in their mental health, whereas others perceived improvement ( 4 , 5 ). A recent study showed that depression and anxiety symptoms worsened and increased among adolescents during the pandemic ( 6 , 7 ). Social connectedness and school disruptions are significantly associated with depressive symptoms ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“… 2 Adolescent high school students are reportedly at high risk for psychological distress, depression, anxiety, loneliness, and trauma symptoms. 3 …”
Section: Introductionmentioning
confidence: 99%